Does tourism effectively stimulate Malaysia's economic growth? - Tang, C.F.; Tan, E.C. (Elsevier, 2015)
This study attempts to further verify the validity of the tourism-led growth hypothesis in Malaysia using a multivariate model derived from the Solow growth theory. It employs annual data from 1975 to 2011. We find that economic growth, tourism and other determinants are cointegrated. Specifically, tourism has a positive impact on Malaysia's economic growth both in the short-run and in the long-run. The Granger causality test indicates that tourism Granger-causes economic growth. All this provides the empirical support for the tourism-led growth hypothesis in Malaysia. In light of this, any policy initiative that promotes tourism could contribute to Malaysia's economic growth. (C) 2014 Elsevier Ltd. All rights reserved.